2022
DOI: 10.1101/2022.10.26.22281529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Programmatic Effectiveness of a Pediatric Typhoid Conjugate Vaccine Campaign in Navi Mumbai, India

Abstract: Background:The WHO recommends vaccines for prevention and control of typhoid fever, especially where antimicrobial-resistant typhoid circulates. In 2018 the Navi Mumbai Municipal Corporation (NMMC), implemented a TCV campaign. The campaign targeted all children aged 9-months through 14-years within NMMC boundaries (~320,000 children) over 2 vaccination phases. The phase 1 campaign occurred from July 14-August 25, 2018 (71% coverage, ~113,420 children). We evaluated the campaign's programmatic effectiveness in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…This single-dose conjugate vaccine provides immunity against Salmonella Typhi, the causative agent of typhoid fever, and has been recommended by the Strategic Advisory Group of Experts for routine use in countries where typhoid fever is endemic [4,5]. Studies from Nepal, Bangladesh, India, Pakistan and Malawi have shown high efficacy of Typbar in preventing typhoid fever [6][7][8][9][10]. In 2020 a second TCV, TYPHIBEV, was prequalified by WHO and clinical trials are ongoing [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This single-dose conjugate vaccine provides immunity against Salmonella Typhi, the causative agent of typhoid fever, and has been recommended by the Strategic Advisory Group of Experts for routine use in countries where typhoid fever is endemic [4,5]. Studies from Nepal, Bangladesh, India, Pakistan and Malawi have shown high efficacy of Typbar in preventing typhoid fever [6][7][8][9][10]. In 2020 a second TCV, TYPHIBEV, was prequalified by WHO and clinical trials are ongoing [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Infectious Diseases , Dr Seth Ari Sim-Son Hoffman and colleagues [ 19 ] share results from an effectiveness evaluation of a pediatric vaccination campaign using a WHO Prequalified TCV, Typbar-TCV® (Vi polysaccharide conjugated to tetanus toxoid, Bharat Biotech India Ltd., Hyderabad, India). This public sector campaign, which targeted children 9 months to 14 years of age, was conducted by the Navi Mumbai Municipal Corporation (NMMC) in Maharashtra, India in 2018.…”
mentioning
confidence: 99%